1996
DOI: 10.1111/j.1432-1033.1996.0468h.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Yeast Peroxisomal Member of the Family of AMP‐Binding Proteins

Abstract: We established a reverse-genetic approach to identify peroxisomal proteins involved in peroxisomal fatty acid metabolism of Saccharomyces cerevisiae. Putative peroxisomal peripheral membrane proteins were isolated by successive extraction of purified peroxisomes and purified by HPLC and SDS/PAGE. Six proteins were identified by peptide sequence analysis, including acyl-CoA oxidase and a trifunctional enzyme of the peroxisomal /I-oxidation system as well as peroxisomal malate dehydrogenase 3 and carnitine acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 50 publications
(52 reference statements)
4
56
0
Order By: Relevance
“…Equal proportions of pellet (P) and supernatant (S) fractions were analyzed by SDS-PAGE and Western blot analysis using specific antibodies against Idp3p, the integral membrane protein Pex3p (34), Pcs60p (32), and the peroxisomal matrix marker Fox3p (30). As Idp3p is hardly extracted by high salt treatment and totally extracted at pH 11, it behaves like Pcs60p, which is localized in the peroxisomal matrix but is also found loosely associated with the peroxisomal membrane (32). B, protease protection analysis of purified peroxisomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal proportions of pellet (P) and supernatant (S) fractions were analyzed by SDS-PAGE and Western blot analysis using specific antibodies against Idp3p, the integral membrane protein Pex3p (34), Pcs60p (32), and the peroxisomal matrix marker Fox3p (30). As Idp3p is hardly extracted by high salt treatment and totally extracted at pH 11, it behaves like Pcs60p, which is localized in the peroxisomal matrix but is also found loosely associated with the peroxisomal membrane (32). B, protease protection analysis of purified peroxisomes.…”
Section: Discussionmentioning
confidence: 99%
“…Idp3p also does not seem to be tightly associated with the peroxisomal membrane, since part of the protein could be extracted with high salt. The extraction properties of Idp3p are similar to those observed for Pcs60p, a protein of the peroxisomal matrix that is also loosely associated with the peroxisomal membrane (32). To distinguish whether Idp3p is associated with the outer aspects of peroxisomes or whether the protein resides in the peroxisomal lumen, we analyzed the sensitivity of organellar Idp3p to externally added proteases.…”
Section: Peroxisomes Of S Cerevisiae Contain An Nadp-dependentmentioning
confidence: 99%
“…Finally, in addition to the 10 major clades, an outlier containing a single yeast protein (sc6) was noted. This protein, known as Pcs60p or Fatp2, is a peroxisomal protein predicted to have ACS activity (46). We previously reported that Fatp2 belonged to an ACS subfamily that contains fungal, plant, and bacterial, but no mammalian, enzymes (11).…”
Section: Phylogenetic Analyses Of Human and Nonhuman Acs Sequencesmentioning
confidence: 99%
“…The antibodies used were obtained from commercial sources or described previously, namely rabbit anti-Pex13p (Girzalsky et al, 1999), anti-Pex11p (Erdmann and Blobel, 1995), anti-Pcs60p (Blobel and Erdmann, 1996), and anti-green fluorescent protein (GFP; W.H. Kunau, Bochum, Germany) as well Full-length PEX13 and various truncations thereof were fused to the GAL4 binding domain (Gal4p-BD) in vector pPC97.…”
Section: Antibodies and Western Blottingmentioning
confidence: 99%